2012
DOI: 10.1128/jcm.00335-12
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Aspergillus fumigatus Isolates Harboring the TR 34 /L98H Azole Resistance Mechanism

Abstract: A rapid emergence of azole resistance has been observed in Aspergillus fumigatus in The Netherlands over the past decade. The dominant resistance mechanism appears to be of environmental origin and involves the TR 34 /L98H mutations in cyp51A. This resistance mechanism is now also increasingly being found in other countries. Therefore, genetic markers were used to gain more insights into the origin and spread of this genotype. Studies of 142 European isolates revealed that those with the TR 34 / L98H resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
118
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 124 publications
(134 citation statements)
references
References 40 publications
15
118
1
Order By: Relevance
“…Four isolates were identified as azole resistant from a total of 72 A. fumigatus isolates, of which three are highly resistant to ITR and harbor the TR34/L98H mutation that was described previously by Lockhart et al (29) In their ARTEMIS study, a total of eight azole-resistant isolates (itraconazole MIC of Ն16 mg/liter) were recovered from Hangzhou, and all exhibited the TR34/L98H mutation together with S297T and F495I. As did Lockhart et al, we found that the TR34/L98H mutation is still a predominant mutation which is quite common in Europe and some other Asian countries (10,15,17,18,20,36,37). Some evidence suggests that this resistant genotype is likely to have arisen as a side effect of widespread use of agricultural fungicides.…”
supporting
confidence: 59%
“…Four isolates were identified as azole resistant from a total of 72 A. fumigatus isolates, of which three are highly resistant to ITR and harbor the TR34/L98H mutation that was described previously by Lockhart et al (29) In their ARTEMIS study, a total of eight azole-resistant isolates (itraconazole MIC of Ն16 mg/liter) were recovered from Hangzhou, and all exhibited the TR34/L98H mutation together with S297T and F495I. As did Lockhart et al, we found that the TR34/L98H mutation is still a predominant mutation which is quite common in Europe and some other Asian countries (10,15,17,18,20,36,37). Some evidence suggests that this resistant genotype is likely to have arisen as a side effect of widespread use of agricultural fungicides.…”
supporting
confidence: 59%
“…Increasing evidence indicated that A. fumigatus should be able to generate resistance to antifungal drugs via the sexual cycle to allow evolution in response to environmental change (40,43). However, a linkage disequilibrium analysis study from the Netherlands indicated that all the azole-resistant A. fumigatus isolates nested within a single, predominantly asexual, population (44).…”
Section: Discussionmentioning
confidence: 99%
“…The five A. fumigatus CYP51A positions, or hot spots, most frequently undergoing mutations responsible for conferring azole resistance are glycine-54, leucine-98, glycine-138, methionine-220, and glycine-448 (4). G54, G138, M220, and G448 CYP51A point mutations are thought to have arisen during triazole therapy of patients in the clinic (5,6), while TR 34 /L98H and TR 46 /Y121F/T289A may have arisen in the environment in the Netherlands in response to the use of agricultural triazole fungicides (7)(8)(9)(10).…”
mentioning
confidence: 99%